Two cases of thrombohaemolytic thrombocytopenic purpura associated with changes in red cell morphology. Issue 5 (September 1963) - McCormack, P.; O'Brien, D. J.; Oliver, R. A. M.
Abstract : Two adult cases of thrombohaemolytic thrombocytopenic purpura are described. Both showed striking morphological changes in the red cells with increased saline osmotic fragility, in addition to thrombocytopenia and generalized hyaline thrombi affecting small blood vessels. These changes support the hypothesis that this is a triple auto-immune disorder affecting red cells, platelets, and small blood vessels.